PROOF OF TRUTH IN INDUCTIVISM THEORY - Moh Abrar; Hasibuan, Nopriani (International Journal of Multidisciplinary Reseach, 2025)
This research discusses truth that can be proven through inductivism theory. The questions in this research include aspect of what is truth? what is theory of inductivism? and how inductivism theory works in proving truth?. This research uses qualitative methods to explore the meaning of the text. The primary sources are books about truth and inductivism theory such as Paul Wahana's Philosophy of Science, then secondary data as support such as articles related to truth and inductivism theory. This research focuses on analyzing inductivism theory in proving truth. This article tries to explore the position of truth through inductivism theory. Can it be proven to be true? And how inductivism theory proves it. It turns out that the analysis of inductivism theory in proving truth or forming knowledge through scientific methods contains many criticisms. However, this criticism must be seen as a guide to finding alternative solutions to overcome the weaknesses of induction. Criticism of induction can also be interpreted as a form of criticism of science as a whole. The limitations of the induction method in science reveal that scientific truth is not the only type of truth that exists.